A 'Position of Peculiar Responsibility': Quaker Women and Transnational Humanitarian Relief, 1914–24. Issue 2 (December 2016) - Roberts, Siȃn
Abstract : Given the scale of Quaker women's involvement in humanitarian responses to the First World War, they have received remarkably little attention in either Quaker historiography or the study of global conflict in this period. This article explores the responses of a network of Quaker women in Birmingham and their sense of personal responsibility to intervene on behalf of non-combatants affected by the war at home and abroad. It takes the relief work of Florence Barrow in Russia and Poland as a biographical case study to consider issues of motivation and practice, and how women relief workers found opportunity to exercise leadership and authority within Quaker relief structures. The article concludes with a discussion of the cultural transmission of a tradition of global concern within their families and women's meetings, and the role it played in shaping their identities as Quaker women and legitimising their activism.